Diagnostic utility of the autism diagnostic observation schedule in a clinical sample of adolescents and adults. (February 2017) - Langmann, Anika; Becker, Joachim; Poustka, Luise; Becker, Katja; Kamp-Becker, Inge
Highlights: In patients with suspicion of highfunctioning autism, differentiation to other diagnoses, especially personality disorders, is a challenge. ADOS Module 4 has good sensitivity and specificity, with slightly better results for the revised algorithm. For females, sensitivity is lower than for males. The ADOS Module 4 has good diagnostic utility when it is used in combination with other sources of diagnostic information and operated by experienced examiners. Abstract: Background: The Autism Diagnostic Observation Schedule (ADOS) Module 4 was investigated in an independent clinical sample of highfunctioning adolescent and adult males and females with suspected autism spectrum disorder. Special attention was paid to the performance of the ADOS in the subgroups autism spectrum disorders (ASD), personality disorders and disorders with onset usually occurring in childhood and adolescence. Method: The recently revised algorithm and severity scores for Module 4 were used to analyze predictive values compared to the original algorithm in a sample of N = 356, 21% females, age range 12–68 yrs. Results: Both algorithms have good sensitivity and specificity, with slightly better results for the revised algorithm. Diagnostic accuracy is lower for females, older individuals, and individuals with personality disorders or higher intellectual abilities. Conclusion: The revised algorithm has good utility when used as part of a comprehensive assessment procedure conducted by an experienced examiner and including information on developmental history.